(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT. This article provides a brief summary of the information learned about the Writing dictations is a powerful tool for enhancing grammar skills and overall language proficiency. By focusing on auditory comprehension and written expression, dictation exercises can reinforce grammatical rules and improve writing fluency. Here are some effective strategies to utilize dictations for grammar improvement.